DIPG-35. A NOVEL HDAC INHIBITOR IN NEW PATIENT-DERIVED DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG) MODELS. Issue 2 (22nd June 2018) - Biery, Matthew; Myers, Carrie; Girard, Emily; Morris, Shelli; Carmack, Savanna; Noll, Alyssa; Sarthy, Jay; Ferguson, Eric; Mhyre, Andrew; Strand, Andrew; Olson, James; Vitanza, Nicholas
Abstract: Diffuse intrinsic pontine glioma (DIPG) remains a universally fatal childhood cancer with a median survival of less than 1 year. Focal radiation remains the standard of care as surgical resection is impossible and conventional cytotoxic chemotherapy has very limited efficacy. Building on the success of other autopsy-derived DIPG cell cultures, we have created a novel patient-derived cell culture, PBT-14FHTC, characterized by mutations in H3FA3, TP53, and amplifications in PDGFRα and cKIT . Previous work has demonstrated the efficacy of panobinostat, a pan-HDAC inhibitor, against DIPG in vitro and in vivo, though resistance develops. Due to this resistance, as well as the limited blood-brain barrier penetration of panobinostat, it is critical to identify other epigenetic agents able to target DIPG. A screen of next generation HDAC inhibitors identified quisinostat, an HDAC inhibitor with a greater selectivity of HDAC1. In vitro studies demonstrate a IC50 < 50 nM against well-characterized patient-derived DIPG cell cultures SU-DIPG-XIII and SU-DIPG-XVII, as well as similar low nM efficacy in other patient-derived cultures such as SU-DIPG-IV, VUMC-DIPG-10, and our new PBT-14FHTC. For in vivo testing, we developed an orthotopic xenograft model using patient-derived DIPG cells transformed with CMV-mCherry-luciferase that can be evaluated by bioluminescence IVIS imaging without harming or euthanizing the subject. In vivo efficacy studies of quisinostat as a single agent, in combination with other epigenetic modulating agents, and in combination with radiation are currently underway using our patient-derived orthotopic xenograft DIPG mouse model.